Distribution of soil fertility indices in aggregate size fractions under different land-use types for coarse-textured soils of the derived savannah - Ifeanyi-Onyishi, Ifeyinwa; Ezeaku, Peter; Umeugokwe, Chigozie; Ezeaku, Victor; Obalum, Sunday (Brawijaya University, 2024)
The research investigated the distribution of soil fertility indices among aggregate-size fractions across three land-use types (forested, cultivated, and fallow lands) for loamy sand at Ede-Oballa, a derived savannah in southeastern Nigeria. Surface soil samples from these land-use types were air-dried and separated into <0.25 mm, 0.25-0.5 mm, 0.5-1.0 mm, 1.0-2.0 mm, 2.0-4.0 mm, and 4.0-8.0 mm aggregates before analyses. There were significant interaction effects of land-use type and aggregate-size fraction on the distribution of soil particle sizes (sand, silt, and clay) and contents of total nitrogen, available phosphorus, exchangeable bases (Mg2+ and Na+), and exchangeable acidity as well as apparent cation exchange capacity (CEC). Land-use type affected soil pH, K+, Ca+, and percent base saturation but not soil organic carbon (SOC), which was rather unevenly distributed among the aggregate-size fractions. The distribution of most fertility indices, those defining CEC, and SOC content favoured >2.0 mm (large), 0.25-0.5 mm and <0.25 mm (micro-) aggregates, respectively, under cultivated land. However, soil total nitrogen and exchangeable acidity contents were best improved in the largest (4.0-8.0 mm) aggregates under forested and fallow lands, respectively. The study highlights the potential of land-use types generally and arable-crop cultivation specifically to engender aggregates of different sizes with specific roles in improving soil quality and fertility.